Polysaccharides from Probiotics: New Developments as Food Additives - Philippe Michaud; Reeta Rani Singhania; Carlos Ricardo Soccol; Ashok Pandey; Anil Kumar Patel (Food Technology and Biotechnology, 2010)
Microbial polysaccharides with nutraceutical potential and bioactive properties have been investigated in detail during the last few decades. There is an increasing demand in food industries for live microbes or polysaccharides produced by them which assert health benefits other than dietetic constituents. Although there are a large number of exopolysaccharide (EPS)-producing bacteria, the titers are low for commercialization. This manuscript deals with the polysaccharides produced by probiotic strains, with major emphasis on the EPSs, their properties, applications and some of the strategies adopted which would be helpful in better understanding of the process in the near future. Research on the improved EPS biosynthesis is essential for obtaining high yields. Therefore, to reach commercialization, metabolic engineering must be applied.